On the possible role of macrofungi in the biogeochemical fate of uranium in polluted forest soils - Kubrová, Jaroslava; Zigová, Anna; Randa, Zdeněk; Rohovec, Jan; Gryndler, Milan; Krausová, Ivana; Dunn, Colin E; Kotrba, Pavel; Borovička, Jan (Journal of hazardous materials, 2014)
Interactions of macrofungi with U, Th, Pb and Ag were investigated in the former ore mining district of Příbram, Czech Republic. Samples of saprotrophic (34 samples, 24 species) and ectomycorrhizal (38 samples, 26 species) macrofungi were collected from a U-polluted Norway spruce plantation and tailings and analyzed for metal content. In contrast to Ag, which was highly accumulated in fruit-bodies, concentrations of U generally did not exceed 3mg/kg which indicates a very low uptake rate and efficient exclusion of U from macrofungi. In ectomycorrhizal tips (mostly determined to species level by DNA sequencing), U contents were practically identical with those of the non-mycorrhizal fine spruce roots. These findings suggest a very limited role of macrofungi in uptake and biotransformation of U in polluted forest soils. Furthermore, accumulation of U, Th, Pb and Ag in macrofungal fruit-bodies apparently does not depend on total content and chemical fractionation of these metals in soils (tested by the BCR sequential extraction in this study).
Keywords: Soil Pollutants; Mycorrhizae; Česká republika; Fungi; ekosystém; Czech Republic; Uranium; Lead; Silver; látky znečišťující půdu; půda; mykorhiza; Ectomycorrhizae; Thorium; Ecosystem; uran; Bioaccumulation; Soil